Analisis Kualitatif Penyusunan Modul Ajar Berbasis Pendekatan Deep Learning oleh Guru - Triayomi, Ria; Kurniawati, Agnes Fibriana; Manullang, Febriani Rotua (JOEAI (Journal of Education and Instruction), 2026)
This study aims to analyze the quality of teaching module development based on the deep learning approach by teachers at Public Elementary School 124 Palembang, focusing on the alignment of instructional components, integration of higher-order thinking skills (HOTS), and utilization of technology. This descriptive qualitative study involved 26 teachers as subjects, with data collected through documentation studies, interviews, and observations analyzed using the Miles and Huberman model. The results revealed a gap between teachers' conceptual understanding and module development practices. Specifically, only 50% of the module samples demonstrated precise alignment between objectives, indicators, and assessments. Approximately 40% of learning activities were still dominated by lower-order cognitive skills, while HOTS integration and student reflection activities had not been systematically implemented. Furthermore, the use of digital media remained limited to basic platforms, with little interactivity. In conclusion, despite teachers' adaptive commitment, intensive mentoring in instructional planning and strengthening of TPACK competencies are needed to produce teaching modules that effectively facilitate students' critical and reflective thinking skills in accordance with national curriculum standards.   Keywords: Deep Learning, HOTS, Teacher Competence, Independent Curriculum, Teaching Modules